The Crisis of Thought and Ijtihad (American Journal of Islam and Society, 1993)
The Muslim mind experienced a crisis of thought when, duting theearly centuries of the Islamic eta, ijtihad began to be viewed as limitedto legal matters rather than as a methodology for dealing with all aspectsof life. This limited understanding engendered a malaise that allowedtaqlid to attain such prominence and tespectability that its cancetous, constricting,and irrelevant fiqh spread throughout Muslim life. Had ijtihadretained mote of its lexical meaning and cteativity, and had fiqh beenconsidered only one of its uses, perhaps Muslims would have overcomemany of the problems that confronted them. However, this patticularizationof ijtihad confined the Muslim mind, and taqlid eventually led tothe paralysis of its creative abilities.Had ijtihad remained a way of life for Muslims as Allah commanded,they would not have fallen behind in establishing the Islamic sciencesnecessary for their society and civilization. They also would not have hadto watch the reins of leadership fall pass to the West, whose most importantqualification was its ability to engage in creative and scientific teasoning.Although its intellectual tradition was tainted with pagan Greekinfluences, the West achieved world leadetship. Had Muslims taken upthose sciences and laid the foundations of society on the basis of tawbd(unity), the face of the earth would be different today and the state of civilizationitself would be fat more felicitous than it is at present.Before ijtihad was confined to the purely legalistic framework of fiqh,the Muslim mind was enlightened, eager to deal with all manner ofthought, and able to meet challenges, generate solutions, and achieve itsgoals. Had it not been for taqlid and its subduing of the Muslim mind,that mind would have achieved great things. Certainly, a mind with itsbeginnings in the verse, "Read! in the name of your Lord Who created. . ." should be mote than able to renew the ummah's mentality, to continuallyadjust to changing circumstances, and to initiate the sciences ofcivilization at a time when the West was o v e m by wild forest tribes.What Do We Mean by Ijtihad?For the teasons indicated above, we ate calling for a new type of ijtihad.Rather than the ijtihad specified by the scholars of usd, which will ...